Pengaruh Kesadaran Dan Pengetahuan Pajak Terhadap Kepatuhan Pelaporan Surat Pemberitahuan (SPT) Pajak Penghasilan (PPH) Orang Pribadi Guru SMA Di Kecamatan Padang Utara - Tania Dofira; Bambang Irawan (Jurnal Ilmu Administrasi Publik, 2026)
This study was motivated by the importance of tax awareness and knowledge in improving taxpayer compliance in filing Personal Income Tax (PPh) Return (SPT) forms. The level of tax reporting compliance is influenced by taxpayers’ understanding and awareness of their tax obligations. This study aims to determine the level of tax awareness, the level of tax knowledge, the level of compliance in filing Personal Income Tax Returns (SPT PPh), as well as the influence of tax awareness and knowledge on compliance in filing Personal Income Tax Returns (SPT PPh) among high school teachers in Padang Utara Subdistrict. This study used a quantitative approach with descriptive and associative methods. The study population consists of high school teachers in Padang Utara Subdistrict, with a sample size of 40 respondents. Data collection was conducted through the distribution of a questionnaire that had been tested for validity and reliability. Data analysis techniques included descriptive statistical analysis, multiple linear regression, T tests, and the coefficient of determination using SPSS. The results of the study indicate that teachers’ tax awareness falls into the “good” category with an average of 61.43, their tax knowledge falls into the “fairly good” category with an average of 59.70, and their compliance with filing Personal Income Tax Returns (SPT) falls into the “good” category with an average of 63.60. The results of the hypothesis testing indicate that tax awareness and tax knowledge have a positive and significant effect on compliance with Personal Income Tax Return (SPT) filing. Thus, increasing tax awareness and knowledge can improve taxpayer compliance in fulfilling tax reporting obligations.